2023
DOI: 10.3390/ani13121909
|View full text |Cite
|
Sign up to set email alerts
|

Atipamezole Reverses Cardiovascular Changes Induced by High-Dose Medetomidine in Cats Undergoing Sedation for Semen Collection

Anna-Lea R. Diggelmann,
Marco Baron Toaldo,
Rima N. Bektas
et al.

Abstract: This study aimed at describing the change in echocardiographic variables after high-dose medetomidine and the reversal with atipamezole in six cats undergoing sedation for semen collection. Further cardiac Troponin I (cTnI) concentration and the effect of repeated sedation were assessed. Echocardiography was performed before and 20 min after sedation with 0.1 mg/kg medetomidine intramuscularly (IM) for urethral catheterisation. Prior to epididymectomy, S-ketamine was administered intravenously. Twenty minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Transient mild bradycardia has been reported after dexmedetomidine administration in dogs, and no intervention was required [45]. Similarly, in a crossover study in healthy cats by Diggelmann et al ( 2023), the administration of a high dose of medetomidine (100 µg/kg) in cats resulted in marked bradycardia and reduction in cardiac output but not a significant increase in cTnI concentrations [30]. In contrast, the administration of 40 µg/kg dexmedetomidine IM in healthy cats by Côté et al (2022) resulted in similar effects as in the study by Diggelmann et al; however, serum cTnI concentrations were significantly increased [31].…”
Section: Creatinine Cardiac Troponin I and Heart Rate (Hr)mentioning
confidence: 95%
See 1 more Smart Citation
“…Transient mild bradycardia has been reported after dexmedetomidine administration in dogs, and no intervention was required [45]. Similarly, in a crossover study in healthy cats by Diggelmann et al ( 2023), the administration of a high dose of medetomidine (100 µg/kg) in cats resulted in marked bradycardia and reduction in cardiac output but not a significant increase in cTnI concentrations [30]. In contrast, the administration of 40 µg/kg dexmedetomidine IM in healthy cats by Côté et al (2022) resulted in similar effects as in the study by Diggelmann et al; however, serum cTnI concentrations were significantly increased [31].…”
Section: Creatinine Cardiac Troponin I and Heart Rate (Hr)mentioning
confidence: 95%
“…Cardiac troponin I (cTnI) is responsible for actin-myosin inhibition during calcium shortage; troponin T (cTnT) binds to tropomyosin and binds it, whereas troponin C (cTnC) binds calcium to inhibit contraction [27][28][29]. It has been reported that the administration of a 2 -agonists does not alter [30] or increase the concentration of cTnI [31,32] in small animals. Hence, the effect of dexmedetomidine and other commonly administered sedative drugs on myocardial function can be easily and non-invasively assessed by measuring specific cardiac biomarkers such as cTnI in cats [27,31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Romagnoli et al (2016) observed reduced heart rate, increased cardiac preload, and compromised systolic function in domestic cats after medetomidine administration (130 μg/kg; im). Diggelmann et al (2023) assessed cardiological changes in this species, focusing on cardiac troponin I (cTnI) levels, following medetomidine treatment (100 μg/kg; im). However, they found that atipamezole (5 μg/kg; im) effectively restored hemodynamic parameters without a significant increase in cTnI concentrations during sedation reversal.…”
Section: Introductionmentioning
confidence: 99%